Seventy-five years of service: an overview of the College of American Pathologists’ proficiency testing program in histocompatibility and identity testing - Sullivan, H. Cliff; Gandhi, Manish J.; Gaitonde, Sujata; Narasimhan, Ramya; Gendzekhadze, Ketevan; Pandey, Soumya; Roby, Rhonda K.; Maha, George C.; Kaur, Harmeet; Schiller, Jennifer J.; McDowell, Julie; Smith, Maria; et al. (Frontiers in Genetics, 2023)
The Histocompatibility and Identity Testing Committee offers an overview of the College of American Pathologists' (CAP) Proficiency Testing (PT) program, commemorating its significant 75th anniversary in 2024. The CAP PT program has undergone significant growth and evolution over the years, ultimately achieving Centers for Medicare and Medicaid Services approval. In 1979, CAP's partnership with the American Association for Clinical Histocompatibility Testing marked a pivotal moment, leading to the creation of the first proficiency testing survey in 1980. This laid the foundation for various PT programs managed by the CAP Histocompatibility and Identity Testing Committee, including HLA antibody testing, HLA molecular typing, engraftment monitoring, parentage/relationship testing, HLA disease associations and drug risk, and HLA-B27 typing. Each program's distinctive considerations, grading methodologies, and future prospects are detailed here, highlighting the continual evolution of histocompatibility and identity testing PT to support emerging technologies and evolving laboratory practices in the field.